Toxicidade da fração hexânica de frutos e sementes de Ricinus communis L. A Apis mellifera L. e Gallus gallus domesticus L. - Lopes, Juliana Marceli Hofma (2023)
The objective was to evaluate the effect of the hexane fraction of fruits and seeds of Ricinus communis (FHFSRc) on Apis mellifera (Africanized bee) and Gallus gallus domesticus (domestic chicken). Three concentrations of FHFSRc were evaluated, namely, 1%, 1.5% and 2%, in addition to two control treatments, one with distilled water and one with Tween 80® (0.01%). FHFSRc was evaluated on A. mellifera through three different bioassays, Bioassay 1 – Contact of workers with a surface contaminated with FHFSRc; Bioassay 2 - Intake of diet containing FHFSRc by A. mellifera workers e; Bioassay 3 - flight test (vertical displacement). The survival evaluations of A. mellifera in bioassays 1 and 2 occurred after 1, 2, 3, 4, 5, 6, 12, 18, 24, 30, 36, 42 and 48 hours, counting the number of dead bees in each time. After 24 hours, the bees from bioassay 3 were submitted to the vertical displacement test. After analyzing the results obtained in bioassays 1 and 2, it was verified that the exposure of A. mellifera workers to FHFSRc, regardless of the concentration or form of exposure used, caused a reduction in the probability of survival, as well as, FHFSRc altered the vertical displacement of A. mellifera. FHFSRc was analyzed on G. gallus domesticus embryos in two different ways of exposure: i) injection of treatments into the air chamber of the egg and ii) spraying of treatments on the egg. The eggs of G. gallus domesticus, after three days of incubation, were collected for morphological analysis using the total mounting technique. After the analysis, it was observed that their exposure to FHFSRc, regardless of the concentration or form of exposure used, caused a reduction in the probability of survival of G. gallus domesticus, as well as, FHFSRc caused malformations in the embryos of G. gallus domesticus when injected into the air chamber. FHFSRc is toxic to A. mellifera workers, negatively interfering with their vertical displacement, in addition to causing a reduction in the probability of survival. FHFSRc is also toxic to G. gallus domesticus embryos, reducing their probability of survival both when injected into the air chamber and when sprayed on the eggshell, and also causing body malformations in G. gallus domesticus embryos when injected into their chamber air.